Design, fabrication, and performance of a flextensional transducer based on electrostrictive polyvinylidene fluoride-trifluoroethylene copolymer - Cheng, ZhongYang (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2002)
Taking advantage of the high electrostrictive strain and high elastic energy density of a newly developed electrostrictive polymer, modified poly(vinylidene fluoride-trifluoroethylene) [P(VDF-TrFE)] based polymers, a flex-tensional transducer was designed, and its performance was investigated. The flextensional transducer consists of a multilayer stack made of electrostrictive P(VDF-TrFE) polymer films and two flextensional shells fixed at the ends to the multilayer stack. Because of the large transverse strain level achievable in the electrostrictive polymer and the displacement amplification of the flextensional shells, a device of a few millimeters thick and lateral dimension about 30 mm x 25 mm can generate an axial displacement output of more than 1 mm. The unique flextensional configuration and the high elastic energy density of the active polymer also enable the device to offer high-load capability. As an underwater transducer, the device can be operated at frequencies below 1 kHz and still exhibit relatively high transmitting voltage response (TVR), very high source level (SL), and low mechanical quality factor (Qm)